Research on the Power Recovery of Diesel Engines with Regulated Two-Stage Turbocharging System at Different Altitudes. (26th March 2014) - Li, Hualei; Shi, Lei; Deng, Kangyao
Abstract : Recovering the boost pressure is very important in improving the dynamic performance of diesel engines at high altitudes. A regulated two-stage turbocharging system is an adequate solution for power recovery of diesel engines. In the present study, the change of boost pressure and engine power at different altitudes was investigated, and a regulated two-stage turbocharging system was constructed with an original turbocharger and a matched low pressure turbocharger. The valve control strategies for boost pressure recovery, which formed the basis of the power recovery method, are presented here. The simulation results showed that this system was effective in recovering the boost pressure at different speeds and various altitudes. The turbine bypass valve and compressor bypass valve had different modes to adapt to changes in operating conditions. The boost pressure recovery could not ensure power recovery over the entire operating range of the diesel engine, because of variation in overall turbocharger efficiency. The fuel-injection compensation method along with the valve control strategies for boost pressure recovery was able to reach the power recovery target.